2009
DOI: 10.1016/j.ajhg.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TRPM1 Are a Common Cause of Complete Congenital Stationary Night Blindness

Abstract: Congenital stationary night blindness (CSNB) is a clinically and genetically heterogeneous group of retinal disorders characterized by nonprogressive impaired night vision and variable decreased visual acuity. We report here that six out of eight female probands with autosomal-recessive complete CSNB (cCSNB) had mutations in TRPM1, a retinal transient receptor potential (TRP) cation channel gene. These data suggest that TRMP1 mutations are a major cause of autosomal-recessive CSNB in individuals of European an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 20 publications
10
154
0
2
Order By: Relevance
“…31 Our patient has a markedly abnormal ERG with a depressed b-wave, a finding consistent with loss of TRPM1 and CSNB. [18][19][20][21] It is possible that the differential expression of LUM in the proband may be secondary to an indirect effect of CSNB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Our patient has a markedly abnormal ERG with a depressed b-wave, a finding consistent with loss of TRPM1 and CSNB. [18][19][20][21] It is possible that the differential expression of LUM in the proband may be secondary to an indirect effect of CSNB.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CHRNA7 deletion is posited to cause seizures and neuropsychiatric disturbances, homozygous TRPM1 (transient receptor potential cation channel, subfamily M, member 1) deletion appears to cause visual impairment, in particular congenital stationary night blindness (CSNB). [17][18][19][20][21] Although analysis of structural variants are beginning to provide insight into functional genomics, 22 the exact relationships between altered CHRNA7 and TRPM1 gene expression, the associated abnormal phenotypes, and the roles of the other genes within the deleted region remain unclear. It is entirely possible that the pathogenic mechanisms underlying CHRNA7 and TRPM1 loss are a direct consequence of the deletion.…”
Section: Introductionmentioning
confidence: 99%
“…These cells express the metabotropic glutamate receptor, mGluR6 [47 -51]. Activation of mGluR6 by glutamate leads, via an intracellular cascade, to the closure of TrpM1 channels on the dendrites of ON-BCs [52][53][54]. Glutamate induces a hyperpolarization of these neurons.…”
Section: General Neuronal Processing In the Outer Plexiform Layermentioning
confidence: 99%
“…Soon after, it was shown that ON bipolar cell function was absent or severely impaired in a mouse model that lacked TRPM1 expression (2-4), although there is evidence that one or more classes of cone-driven ON bipolar cells may use an additional channel (3). Mutations in TRPM1 have now been positively linked to CSNB in humans as well (5)(6)(7). Taken together, studies of mouse, horse, and human provide convincing evidence that the ON bipolar cell transduction channel is composed of TRPM1, either alone or in conjunction with other channels.…”
mentioning
confidence: 99%